A review of the world Cyphocarididae with description of three new species (Crustacea, Amphipoda, Lysianassoidea) - Hughes, Lauren E.; Lowry, James K. (Zootaxa, 2015)
The world Cyphocarididae are reviewed with new distribution records provided for eight taxa including three new species of Cyphocaris, C. ananke, C. nesoi and C. tartaros. Based on collections from Greenland a neotype is established for the type species Cyphocaris anonyx Boeck, 1871. An updated key to the 17 known world species of cyphocarids is provided.